Religious elements in the statutes of political parties in Serbia - Vinokić, Milana (Sociološki pregled, 2025)
The main aim of the research is to examine the presence of religious elements in the statutes of political parties in Serbia. The hypothesis is that certain parties, even if they do not appear to have a religious orientation, contain religious elements in their statutes and thus send certain religious messages to their voters. To examine this, an analysis of the content of 115 statutes of political parties in Serbia was conducted. The results show the presence of religious elements in 79.1% of the analyzed statutes. Some parties favour one specific religious community (most often the Serbian Orthodox Church). Namely, political parties in Serbia utilize religion in their statutes as an instrument for constructing and maintaining collective identity, as well as legitimizing their political objectives.